2006
DOI: 10.1063/1.2164907
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic analysis of optical gain in InGaN∕GaN quantum wells

Abstract: A microscopic theory is used to analyze optical gain in InGaN∕GaN quantum wells (QW). Experimental data are obtained from Hakki–Paoli measurements on edge-emitting lasers for different carrier densities. The simulations are based on the solution of the quantum kinetic Maxwell–Bloch equations, including many-body effects and a self-consistent treatment of piezoelectric fields. The results confirm the validity of a QW gain description for this material system with a substantial inhomogeneous broadening due to st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…One of the most important stages of the device improvement is an investigation of active region amplification features. Although many techniques of semiconductor gain measurements have been developed [1][2][3] the question concerning the physics of this process in nitride-based materials has been still brought up in numbers of publications [4][5][6]. Carrier dependent gain spectra have been theoretically determined taking into account internal piezoelectric fields, homogeneous broadening due to carrier-carrier and carrier-phonon scattering, bandfilling, Coulomb induced band gap renormalization and it's random fluctuation [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important stages of the device improvement is an investigation of active region amplification features. Although many techniques of semiconductor gain measurements have been developed [1][2][3] the question concerning the physics of this process in nitride-based materials has been still brought up in numbers of publications [4][5][6]. Carrier dependent gain spectra have been theoretically determined taking into account internal piezoelectric fields, homogeneous broadening due to carrier-carrier and carrier-phonon scattering, bandfilling, Coulomb induced band gap renormalization and it's random fluctuation [7].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand these gain spectra act as reference for microscopic gain simulations (Witzigmann et al 2006;Hader et al 2006). On the other hand we extract several parameters as input for the rate-equation model of the laser dynamics: differential gain, gain dispersion (i.e.…”
Section: Optical Gainmentioning
confidence: 99%
“…The nonuniform emission intensity across the emission aperture with several bright emission spots was observed. The earlier report showed that InGaN MQWs tend to have indium inhomogeneity [50]; thus, we believe that the nonuniformity in the emission intensity across the aperture could be due to the indium nonuniformity that creates nonuniform spatial gain distribution in the emitting aperture. Actually, we observed that the lasing action mainly arises from the spots with brightest intensity, as indicated in the inset of Fig.…”
Section: Characteristics Of Electrically Pumped Gan-based Vcselmentioning
confidence: 99%